A Rare Complication of Implantable Cardiac Defibrillator Placement - Ferreira, João André dos Santos (J Cardiovasc Echogr, 2020)
Implantable cardiac defibrillators (ICDs) are a popular and effective option in heart failure with left ventricular systolic dysfunction patients. Although frequently underdiagnosed, inadvertent malposition can lead to endocardial damage and thrombotic events. As ICD implants tend to increase in the following years, the recognition of their complications is critical. The authors present a case of a 64-year-old female with advanced heart failure and ICD malposition. This accidental discovery was denounced by the presence of a right bundle branch block (RBBB) pattern and later confirmed by echocardiography which showed the lead tip in contact with the midsegment of the left ventricular anterolateral wall. As the patient's hospitalization was complicated with refractory ascites and cardiogenic shock, she underwent cardiac transplantation, with no recurrence of heart failure symptoms. An electrocardiogram showing a RBBB pattern during VVI pacing should arise the suspicion of inadvertent incorrect placement of a pacing/ICD lead. The many facets of echocardiography should be used for the diagnosis of this complication, as they were paramount in this case, as highlighted.